Can we explain AMS-02 antiproton and positron excesses simultaneously by nearby supernovae without pulsars or dark matter?. (11th February 2016) - Kohri, Kazunori; Ioka, Kunihito; Fujita, Yutaka; Yamazaki, Ryo
Abstract: We explain the excess of the antiproton fraction recently reported by the AMS-02 experiment by considering collisions between cosmic-ray protons accelerated by a local supernova remnant and the surrounding dense cloud. The same "$pp$ collisions" provide the right ratio of daughter particles to fit the observed positron excess simultaneously in the natural model parameters. The supernova happened in relatively lower metallicity than the major cosmic-ray sources. The cutoff energy of electrons marks the supernova age of ${\sim }10^{5}$ years, while the antiproton excess may extend to higher energy. Both antiproton and positron fluxes are completely consistent with our predictions in an earlier paper [Y. Fujita et al., Phys. Rev. D 80, 063003 (2009) [arXiv:0903.5298 [astro-ph.HE]]].